How did you hear the news? The role of traditional media, social media, and personal communication in flashbulb memory. (August 2019) - Talarico, Jennifer M; Kraha, Amanda; Self, Heather; Boals, Adriel
Flashbulb memories are at the intersection of public and private event memory. We investigated whether the source of news (traditional media, social media, or another person) shaped how people remembered learning of an event. Individuals were asked how they learned of Osama bin Laden's assassination immediately after the event and 7, 42, 224, or 365 days later. Initial memory reports from those who learned from traditional media showed enhanced phenomenological features (i.e., a sense of recollection and vividness) relative to those who learned from social media or from another person. Both phenomenological and metacognitive (i.e., belief in the memory's accuracy) features of memory reports decreased over time; however, there were no differences as a function of source. Consistency of the memory reports did not differ as a function of time or source. Although sources differed as a function of social group salience, these differences did not seem to influence memory.